Analisis Yuridis Pembatalan Pendaftaran Paten Sederhana - Pranacitra, Rendy (Fakultas Hukum Universitas Trisakti, 2022)
Human intellectual technological inventions are protected by the granting of patent rights. Simple patents are an important part of industry progress. The era of globalization of industrial competition has influenced the development of national markets that have an impact on the competition of international markets. The problem in this study is whether a simple patent that has already been registered can be requested for cancellation and whether the judgment of the Commercial Court No. 61/Pdt.Sus-Paten/2018/PN.Niaga.Jkt.Pst has been in accordance with Law No. 13 Year 2016 on Patents. The research methods used are normative jurisprudence using secondary data, qualitative descriptive data analysis and deductive inference. The results of the study show that under article 130 of the Law No. 13 Year 2016 Patents, registered patents can be sought for cancellation of registration as cancelled by law, or on request, and/or cancellations of patents as litigation. Decision of the Chamber of Judges of the Trade Court of Jakarta Central No. 61/Pdt.Sus-Paten/2018/PN.Niaga.Jkt.Pst stating that the “claims of the Claimants are not admissible” on the grounds of “deficient claims” is inappropriate, because in its consideration the judge only referred to Article 10 para. (2) of Law No. 13 Year 2016 but did not take into account Article 12 para. (1) and (2) of the Law Number 13 Year 2016.